The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/ma13235556
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilm Formation Using PCL/Curcumin Electrospun Fibers and Its Potential Use for Biotechnological Applications

Abstract: Electrospun nanofibers are used for many applications due to their large surface area, mechanical properties, and bioactivity. Bacterial biofilms are the cause of numerous problems in biomedical devices and in the food industry. On the other hand, these bacterial biofilms can produce interesting metabolites. Hence, the objective of this study is to evaluate the efficiency of poly (Ɛ- caprolactone)/Curcumin (PCL/CUR) nanofibers to promote bacterial biofilm formation. These scaffolds were characterized by scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
(111 reference statements)
2
9
0
Order By: Relevance
“…In this work, a 13% solution of PCL in THF was prepared. Similar concentrations have been previously reported for the successful preparation of fibers [ 56 , 57 , 68 ]. Moreover, studies have reported that chloroform, as well as THF, have been used to successfully electrospun PCL fibers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this work, a 13% solution of PCL in THF was prepared. Similar concentrations have been previously reported for the successful preparation of fibers [ 56 , 57 , 68 ]. Moreover, studies have reported that chloroform, as well as THF, have been used to successfully electrospun PCL fibers.…”
Section: Discussionsupporting
confidence: 80%
“…In this work, PCL fibers were chosen to be enriched with carbon and nitrogen sources, as PCL fibers have been reported to have a minimal effect on bacterial cell growth [ 17 , 53 , 54 , 55 , 56 , 57 ]. From the tested bacteria in this study, PCL fibers did not elicit any decrease in cell growth for P. aeruginosa ( Figure 5 ), as observed in a previous report, where the cell growth of P. aeruginosa and S. epidermidis was not affected with PCL fibers after 6 h of incubation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be associated with the filling nature of curcumin as an additional component in the spinning solution. The increase in the average diameter after curcumin incorporation has also been demonstrated in previous studies [49][50][51].…”
Section: Nanofibers Characterizationsupporting
confidence: 80%
“…The next study describes the effectiveness of electrospun curcumin-loaded PCL homogeneous nanofibers with diameters ranging from 441 to 557 nm to support the formation of bacterial biofilm. 32 Interestingly, the authors used a solution preparation method different from the other studies: curcumin was preliminarily dissolved in ethanol with further addition into 10% PCL chloroform solution at various proportions (from 2.0 to 10.0% v/v). As a result, the nanofibers obtained allow the prevention of pathogenic biofilm formation caused by the three bacteria strains: Pseudomonas aeruginosa , Staphylococcus aureus and Escherichia coli .…”
Section: Polymers Used For Curcumin-loaded Fiber Formationmentioning
confidence: 99%